2020
DOI: 10.3389/fendo.2020.00309
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up and Outcomes of Autoimmune Thyroiditis in Childhood

Abstract: Background: Autoimmune thyroiditis (AIT) is the most common cause of acquired hypothyroidism in children. The natural outcome of AIT in childhood has been reported previously however follow-up duration is generally short and results variable.Objectives: To characterize clinical and biochemical findings at presentation of AIT, evaluate long-term outcomes and assess which factors at presentation predict evolution over time.Study cohort: 201 children under 18 years of age at presentation (82% female) were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 30 publications
4
21
5
Order By: Relevance
“…Further analysis of the data revealed that the male proportion was dominant in patients under 2 years old. The female-to-male ratio in 2-3-year-old patients was 5.5:1, which is similar to the previously published results (5,6,25). In-line with our findings, Foley et al (9) reported four patients with HT aged between 9 months and 2 years, of which three were boys and only one was a girl.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Further analysis of the data revealed that the male proportion was dominant in patients under 2 years old. The female-to-male ratio in 2-3-year-old patients was 5.5:1, which is similar to the previously published results (5,6,25). In-line with our findings, Foley et al (9) reported four patients with HT aged between 9 months and 2 years, of which three were boys and only one was a girl.…”
Section: Discussionsupporting
confidence: 92%
“…In a study of children and adolescents with HT, females were shown to have an increased incidence of HT with a female-tomale ratio of 4~5:1 (5,6,25). However, in this study, the female-to-male ratio was only 1.7:1, which was significantly lower than what has been previously reported (5,6,25).…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…In the case of hypothyroidism, levothyroxine can be effective for goiter shrinkage as well as for maintaining the euthyroid state. 11) The normalization of thyroid function has been found to occur in 16-50% of children with hypothyroidism resulting from HT. To treat the pain associated with HT in adults, oral prednisolone and NSAIDs, as well as levothyroxine, are recommended.…”
Section: Discussionmentioning
confidence: 99%